Manifestaciones clínicas de la leucemia aguda en los niños hospitalizados en Trujillo durante el periodo 2008 - 2014 - León Vera, Joe Leo (2017)
Objective: To determine the frequency of clinical manifestations of acute leukemias (LA) in hospitalized children in Trujillo during the period 2008-2014. Material and Methods: Retrospective, transversal and descriptive study. We reviewed 146 medical records of patients under 18 during the period from January 2008 to December 2014 with diagnosis of Acute Leukemia of the 3 hospitals level III in Trujillo, being selected only 123 medical records. The data were collected in ad hoc form and were stimated frequencies of the most frequent findings. Results: In the study period, 123 medical records of acute leukemia were selected, 118 corresponded to acute lymphoid leukemia (LLA) and only 5 cases to acute myeloid leukemia (LMA). Of these, 65 were men and 58 women. The mean age of the cases was 7.87 ± 5.46. Within the initial clinical manifestations of LLA the more frequent were: pallor (39.02%), fever (27.64%); while in LMA were: pallor (80%), osteoarticular pain (40%) .Within the clinical manifestations during the hospitalization of LLA were: hepatomegaly (46.34%), lymphadenopathy (43.09%); while in LMA were: hepatomegaly (80%), splenomegaly (60%). Conclusions: Clinical manifestations of LLA were: pallor, fever; while in LMA were: pallor, osteoarticular pain. Within the clinical manifestations during the hospitalization of LLA were: hepatomegaly, lymphadenopathy; while in LMA were: hepatomegaly, splenomegaly.